Use of somotosensory-stimulus interventions to improve gait stability - Loh, Yee Siang. (2011)
The purpose of this project was to investigate the effect of different body supports on human stability during normal walking condition and evaluate the kinematic variability and local dynamic stability of lower body. It was to determine which part of lower body is the best position to mitigate instability in order to improve balance control related to gender and age differences. Five different types of scenario (no support, ankle support, shank support, knee support and thigh support) were applied to two groups (age below 55 and above 55) of eight participants (4 males and 4 females) each. Three-dimensional movements of 26 infrared markers were placed over the body and motions were recorded during the continuous walking at preferred walking speed (PWS) of the participants. Mean stride to stride, step length and walking speed were computed to quantify kinematic variability and local dynamic stability. Subjects with knee support performed better stability control at normal walking speed compare to ankle support, shank support and thigh support. Their stride length, mean velocity became shorter and slower even at the cost of increased variability. These experimental results will be useful for the researchers and clinicians to evaluate and improve the elderly’s stability by designing body support mechanism to prevent them from falling down.